BIODEGRADATION OF STYROFOAM WASTE BY HONGKONG MEALWORMS (Tenebrio molitor) - Kurniani, Riska; Ruyani, Aceng; Johan, Henny; Defianti, Aprina; Yani, Ariefa Primair; Listiono, Arsela Eko (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2025)
This research aims to describe the ability of mealworms (Tenebrio molitor) to reduce styrofoam waste by observing the decrease in styrofoam weight and survival rate over one week. The method used is an experiment with a Completely Randomized Design (CRD) with 4 treatments (P0, P50, P100, P150) and 4 replications. The data was analyzed using descriptive statistics. The research stages include container preparation, larvae, stocking, feeding, and maintenance. The results show that the weight loss of styrofoam occurred at P50 (18.5%), P100 (22.75%), and P150 (36%). Meanwhile, the control group (P0) only experienced a weight loss of 1.5%. This indicates that the greater the number of T. molitor, the greater the weight loss of styrofoam. The highest survival rate for T. molitor was observed at P50, with a decrease in numbers of only 12.5%. At P150, the decrease was 16.8%, and at P100, it was 28.75%. This decrease is suspected to be caused by competition among T. molitor, population density, and a lack of nutrients despite the addition of supplementary feed. Based on the analysis of the results, it can be concluded that T. molitor is capable of reducing styrofoam waste, with the highest survival rate in the P50 group.